The Use of Teaching British Parliamentary Debate through Android Application, Video, and Powerpoint Presentation to Improve the Students’ Speaking Skills - Surya Agung Wijaya (Register Journal, 2016)
The researcher conducted the study to increase the students’ speaking skills through Android application, video, and PowerPoint Presentation in teaching British Parliamentary Debate. This study answers two questions (1) How is the implementation of teaching British Parliamentary Debate through Android application, video, and PowerPoint Presentation at English Debate Club in SMK N2? (2) To what extent is the improvement of teaching British Parliamentary Debate through Android application, video, and PowerPoint Presentation at English Debate Club in SMK N2 to improve the students’ speaking skills?. The research design of this study was Classroom Action Research. It had three cycles. Each cycle consisted of planning, acting, observing, and reflecting. From the study, the researcher could conclude that the implementation of the study improved gradually from cycle 1, cycle 2, and cycle 3. The improvement of the study was showed when the researcher conducted cycle 3. The result of the t-test of cycle 3 was 2.56. Before the impact has not seen by the researcher in the cycle 1 and cycle 2, the result of the t-test of cycle 1 and 2 was 1. The passing grade was 72, and the target of the passing grade was 85%. The result of the post-test of cycle 3 was 90.91% from students. They passed the passing grade. The passing grade of cycle 3 was over the target, so the researcher stopped the study. Thus, instruments proved that it could improve the students’ speaking skills.